2018
DOI: 10.1002/adma.201705333
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Bonding of Thermoplastics to Rubbers for Printable, Reel‐to‐Reel Processing in Soft Robotics and Microfluidics

Abstract: The lamination of mechanically stiff structures to elastic materials is prevalent in biological systems and popular in many emerging synthetic systems, such as soft robotics, microfluidics, stretchable electronics, and pop-up assemblies. The disparate mechanical and chemical properties of these materials have made it challenging to develop universal synthetic procedures capable of reliably adhering to these classes of materials together. Herein, a simple and scalable procedure is described that is capable of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Further, by extending this deposition strategy to other functional inorganic materials, we could construct new variants of plastic/metal hybrid structures not easily accessible using other strategies. We believe that the methods and concepts presented herein (as represented by µ‐DECD) are unique in acheiving patterned depostion through confinement of the surface‐chemi‐cal processes within the microchannels without the need for sophisticated instruments, and are applicable to a variety of emerging technologies including: functional substrates for smart textiles, disposable healthcare monitoring systems, remotely controlled/powered soft robots (e.g., those that use polymeric films with metallic traces for communication or inductive coupling), antennas,[17a,b] and a range of low‐cost sensing electronics …”
Section: Resultsmentioning
confidence: 99%
“…Further, by extending this deposition strategy to other functional inorganic materials, we could construct new variants of plastic/metal hybrid structures not easily accessible using other strategies. We believe that the methods and concepts presented herein (as represented by µ‐DECD) are unique in acheiving patterned depostion through confinement of the surface‐chemi‐cal processes within the microchannels without the need for sophisticated instruments, and are applicable to a variety of emerging technologies including: functional substrates for smart textiles, disposable healthcare monitoring systems, remotely controlled/powered soft robots (e.g., those that use polymeric films with metallic traces for communication or inductive coupling), antennas,[17a,b] and a range of low‐cost sensing electronics …”
Section: Resultsmentioning
confidence: 99%
“…Taylor, et al recently demonstrated a simple chemical platform that enables the bonding of many types of commercial polymers (with glass transition temperatures < 150°C) to pure silicone. [50] In Figure 6b,ii we also show that, due to both the elasticity of the silicone and the shape memory effect in the PLA variable stiffness sheet, [51,52] the material is able to recover some of the set shape when reheated after shape fixing. The ~90° bend flattened itself, recovering 69% of its bend, and the twisted 180° sample was able to recover 66% of its twist (see also Supplemental Video 4).…”
Section: Reversible Shape Changementioning
confidence: 89%
“…Researchers describe a simple procedure to covalently bond commercial thermoplastic to silicone rubbers, in which (3‐ami‐nopropyl)triethoxysilane is used to aminate the surface of oxidized thermoplastics and oxidized by ultraviolet–ozone. Combining with laser printing, microfluidic devices can be directly fabricated in a low‐cost manner (Figure B) . This strategy demonstrates a new approach to the fabrication of microfluidic devices with advantages of process scalability and material diversity.…”
Section: Materials For Microfluidic Devicesmentioning
confidence: 99%
“…B) Laser printing of microfluidic devices by covalent bonding of thermoplastics to rubbers. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Materials For Microfluidic Devicesmentioning
confidence: 99%